Relationship Between Breakfast Intake with Mood and Short-Term Memory Among Medical Students of Pelita Harapan University : A Cross Sectional Study - Yang Yang Endro Arjuna; Dwi Savitri Rivami (Medicinus, 2022)
Introduction: Epidemiological studies stated people rarely eat breakfast even though breakfast has an important role in human physicality, mood, and short-term memory. The mood is the tone of feelings a person feels, while short-term memory is part of the cognitive system used to store memories for a short time. Aims: This research was conducted to determine the relationship between breakfast with mood and short-term memory among Medical Students of Pelita Harapan University.Methods: This study used a cross-sectional study carried out on 133 students who were obtained based on the method of calculating, unpaired categorical comparative analytic samples. The sample population was taken by judgmental sampling on active students of the Faculty of Medicine, the University of Pelita Harapan in 2020 according to the inclusion and exclusion criteria. Data were collected using a self-administered questionnaire, Positive and Negative Affect Schedule, Digit Span Test Forward Span. The statistical test used was Chi-square and Fisher Exact, with data processing using Microsoft Excel 2019 and SPSS 24.0.Results: There were 133 samples based on inclusion and exclusion criteria. The majority of the sample was female (54.1%), batch 2018 (37.6%), 20 years old (36.8%), used to breakfast (62.4%), had a positive mood (96.2%), optimal short-term memory (64.7%). The result showed no significant between breakfast intake with mood (OR 2.585; 95%CI (0.417-16.034); p=0.364) and a significant relationship between breakfast intake with short-term memory (OR 2.773; 95%CI (1.325-5.801); p=0.011).Conclusions: There was no significant relationship between breakfast intake with mood, and a significant relationship between breakfast intake and mood was found. Further studies with larger samples are needed to minimize biases in future studies.